The Change of Skeletal Muscle Caused by Inflammation in Obesity as the Key Path to Fibrosis: Thoughts on Mechanisms and Intervention Strategies - Yixuan Li; Wenwen Guo; Han Li; Yuhao Wang; Xinwei Liu; Wen Kong (Biomolecules)
Obesity leads to a chronic inflammatory state throughout the body, with increased infiltration of immune cells and inflammatory factors in skeletal muscle tissue, and, at the same time, the level of intracellular mitochondrial oxidative stress rises. Meanwhile, obesity is closely related to the development of skeletal muscle fibrosis and can affect the metabolic function of skeletal muscle, triggering metabolic disorders such as insulin resistance (IR) and type 2 diabetes (T2D). However, whether there is a mutual regulatory effect between the two pathological states of inflammation and fibrosis in obese skeletal muscle and the specific molecular mechanisms have not been fully clarified. This review focuses on the pathological changes of skeletal muscle inflammation and fibrosis induced by obesity, covering the metabolic changes it causes, such as lipid deposition, mitochondrial dysfunction, and dysregulation of inflammatory factors, aiming to reveal the intricate connections between the two. In terms of intervention strategies, aerobic exercise, dietary modification, and pharmacotherapy can improve skeletal muscle inflammation and fibrosis. This article provides insight into the important roles of inflammation and fibrosis in the treatment of obesity and the management of skeletal muscle diseases, aiming to provide new ideas for the diagnosis and treatment of metabolic diseases such as obesity and IR.